Game Education Construct 2 : Generation Z Science Learning Solutions - Handoko*, Akbar; Sodikin, Sodikin; Rakhmawati, Ismi (Universitas Syiah Kuala, 2023)
The use of learning media is very important for students for the learning process as an intermediary to convey messages or information. Game education can affect the cognitive function and motivation of students and stimulate the curiosity of learners, especially when entering tantagan and fantasy elements into an educational game. The purpose of this study is to determine the feasibility of learning media in the form of educational game applications on respiratory system material and student responses in its use. In this study, the media developed was in the form of a construct 2-based game education. This type of research is RD using a model developed by Robert Maribe Branch, namely the ADDIE model. The results of the research obtained learning media in the form of decent and interesting based game education to be used as learning media. With the average percentage of validation assessments obtained from 85.18% from media experts, 94.79% from material experts and 93.75% from linguist assessments with the category of very decent. The use of game education learning media by students received a response of 81.25% which showed that the media was very interesting and worth using, these results were obtained through filling out questionnaires conducted using two classes